Body and nature in Job - Viviers, Hennie (Old Testament essays, 2001)
The 'languaging' of the body and the 'embodiment' of society enlighten the formation of culture. As an epistemological agency the notion 'body' also markedly enlightens the understanding of the human condition, the human as a symbolising being. In this article the reciprocity between body and nature in the book of Job is investigated. The focus is especially on the Divine Address (Job 38:1-42:6), apparently intended by the author as a cosmological system to locate unjust suffering meaningfully. The how of the metaphoric extension of the body as microcosm to (body) nature as macrocosm is highlighted. Personification of nature, the notion of mutual incorporation, nature as ground metaphor or symbol for human life and corporeally based image schemata, inter alia receive attention. Some brief comments are also made on the alternative ideology the projected cosmic body, as a new symbolic system, intends to promote.